Toxicity of different forms of antimony to rice plants: Effects on reactive oxidative species production, antioxidative systems, and uptake of essential elements. (August 2020) - Zhu, YanMing; Wu, QianHua; Lv, HaiQin; Chen, WenXiang; Wang, LiZhen; Shi, ShengJie; Yang, JiGang; Zhao, PingPing; Li, YuanPing; Christopher, Rensing; Liu, Hong; Feng, RenWei
Abstract: Antimonite [Sb(III)] and antimonate [Sb(V)] are known to have different toxicity to plants, but the corresponding mechanisms are not fully understood. This study was conducted to investigate reactive oxygen species (ROS), antioxidant systems, and levels of certain essential elements in response to exposure to Sb(III) and Sb(V). Results showed that exposure to Sb(V) caused oxidative stress in a rice plant (Yangdao No.6). Sb(III) was shown to be more toxic than Sb(V) as judged from a lower shoot biomass, a higher loss of essential elements, and higher production of superoxide anion free radicals (O2 − ). The toxicity of Sb(III) might partially be due to the disturbance of the O2 ˉ dismutation reaction, which resulted in root cell membrane damage under exposure to 20 mg L −1 Sb(III). Sb(V) stimulated the shoot fresh weight and the shoot uptake of many essential elements. Moreover, Sb(V) and Sb(III) both stimulated the accumulation of calcium in the shoots and roots, and calcium was found to significantly correlate with the concentrations of many essential elements and with some parameters correlated to antioxidant systems, suggesting a Ca-induced regulatory mechanism. The activity of glutathione peroxidase was significantly enhanced by Sb(V) and Sb(III), suggesting a role in scavenging hydrogen peroxide. Catalase was activated by exposure to 20 mg L −1 Sb(III) in the roots and by exposure to 20 mg L −1 Sb(V) both in the shoots and roots. However, peroxidase was activated by exposure to 5 mg L −1 Sb(III) in the shoots and by exposure to 5 mg L −1 Sb(V) in the roots. This study, for the first time, showed the differences between Sb(V) and Sb(III) toxicity when looking at the antioxidant response and essential element uptake. Graphical abstract: Image 1 Highlights: Sb(III) and Sb(V) exposure will both produce oxidative stress in plants. O2 ˉ : H2 O2 ratio increased with Sb(III) treatment levels but it reversed under high Sb(V) exposure. Ca uptake was up-regulated by both Sb(III) and Sb(V) in the shoots and roots. Higher toxicity of Sb(III) than Sb(V) was related to increased loss of most essential elements. GSH-Px activity was activated by Sb(III) and Sb(V), but CAT and POD were not always activated.